2010
DOI: 10.4103/0019-5413.65134
|View full text |Cite
|
Sign up to set email alerts
|

Resection-reconstruction arthroplasty for giant cell tumor of distal radius

Abstract: Background:Giant cell tumor (GCT) of the distal radius poses problems for reconstruction after resection. Several reconstructive procedures like vascularized and non-vascularized fibular graft, osteo-articular allograft, ceramic prosthesis and megaprosthesis are in use for substitution of the defect in the distal radius following resection. Most authors advocate wrist arthrodesis following resection of distal radius and non vascularized fibular graft. Here we have analyzed the results of aggressive benign GCTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
39
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 30 publications
5
39
0
5
Order By: Relevance
“…(8,6,9,10,11,12,7,13,14,17,15,18) The recurrence rate has been reported to be 0% or 5 to 25%. (5,13,19) In our study there was no recurrence. In some series subluxation of wrist has been reported.…”
Section: Discussionsupporting
confidence: 51%
“…(8,6,9,10,11,12,7,13,14,17,15,18) The recurrence rate has been reported to be 0% or 5 to 25%. (5,13,19) In our study there was no recurrence. In some series subluxation of wrist has been reported.…”
Section: Discussionsupporting
confidence: 51%
“…In contrast, in adults, the absence of joint-surface remodeling results in radiocarpal joint incongruity and consequently osteoarthritis and movement limitation [22,29]. The average ROM of the wrist after reconstruction using the fibular autograft has been reported as 20°-38°flexion, 20°-50°extension, 30°-80°pronation, and 15°-52°supination [21,28,30]. Despite osteoarthritic changes and decreased ROM, most patients in those studies [21,28,30] had little limitation in daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…The average ROM of the wrist after reconstruction using the fibular autograft has been reported as 20°-38°flexion, 20°-50°extension, 30°-80°pronation, and 15°-52°supination [21,28,30]. Despite osteoarthritic changes and decreased ROM, most patients in those studies [21,28,30] had little limitation in daily activities. However, the technique has been associated with potential complications such as nonunion, delayed union of the graft, collapse of the grafted fibular head and donor-site morbidity [28,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, reconstruction of the distal radius is a challenge with regard to regaining normal function in the hand with minimal complications. A number of studies have reported on the reconstruction of segmental distal radial defects after tumour resection by using a non-vascularised or vascularised autogenous fibular graft; the reconstruction procedures have mainly included arthroplasty [2,4,[17][18][19][20][21], partial wrist arthrodesis [3,22,23] and complete wrist arthrodesis [24][25][26].…”
Section: Discussionmentioning
confidence: 99%